Vesiduction: the fourth way of HGT. (14th June 2020) - Soler, Nicolas; Forterre, Patrick
Summary: Besides the canonical gene transfer mechanisms transformation, transduction and conjugation, DNA transfer involving extracellular vesicles is still under appreciated. However, this widespread phenomenon has been observed in the three domains of life. Here, we propose the term 'Vesiduction' as a fourth mode of intercellular DNA transfer.